2023
DOI: 10.1021/acs.jpclett.3c01402
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Mutations Alter RNA-Driven Functional Cross-Talk Underlying Premature-Messenger RNA Recognition by Splicing Factor SF3b

Abstract: The pillar of faithful premature-messenger (pre-mRNA) splicing is the precise recognition of key intronic sequences by specific splicing factors. The heptameric splicing factor 3b (SF3b) recognizes the branch point sequence (BPS), a key part of the 3′ splice site. SF3b contains SF3B1, a protein holding recurrent cancer-associated mutations. Among these, K700E, the most-frequent SF3B1 mutation, triggers aberrant splicing, being primarily implicated in hematologic malignancies. Yet, K700E and the BPS recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
3
2
0
Order By: Relevance
“…The latter contains the conserved adenosine acting as the nucleophile in the branching step of splicing. That study, in which the wild-type and the K700E variant of SF3B1 of the protein were considered, revealed that by inducing a cascade of altered salt bridge interactions, K700E weakens and remodels pre-mRNA binding to SF3b, thus scrambling the RNA-mediated allosteric cross-talk between the BPS and mutation site and reducing SF3b faithful selection ability (Figure A–C) . The work corroborated previous findings on the yeast homologues of the SF3b complex …”
Section: Spliceosome: Unravelling Catalytic and Regulatory Mechanism ...supporting
confidence: 89%
See 1 more Smart Citation
“…The latter contains the conserved adenosine acting as the nucleophile in the branching step of splicing. That study, in which the wild-type and the K700E variant of SF3B1 of the protein were considered, revealed that by inducing a cascade of altered salt bridge interactions, K700E weakens and remodels pre-mRNA binding to SF3b, thus scrambling the RNA-mediated allosteric cross-talk between the BPS and mutation site and reducing SF3b faithful selection ability (Figure A–C) . The work corroborated previous findings on the yeast homologues of the SF3b complex …”
Section: Spliceosome: Unravelling Catalytic and Regulatory Mechanism ...supporting
confidence: 89%
“…That study, in which the wildtype and the K700E variant of SF3B1 of the protein were considered, revealed that by inducing a cascade of altered salt bridge interactions, K700E weakens and remodels pre-mRNA binding to SF3b, thus scrambling the RNA-mediated allosteric cross-talk between the BPS and mutation site and reducing SF3b faithful selection ability (Figure 7A−C). 346 The work corroborated previous findings on the yeast homologues of the SF3b complex. 347 An allosteric cross-talk was also observed when cancerassociated mutations are present on the U2AF2 splicing factor responsible for recognizing the poly-Py tract of pre-mRNA (Figure 7D).…”
Section: Regulatory Mechanism and Splicing Modulation By Small Moleculessupporting
confidence: 89%
“…The community fragmentation further increases upon U4 snRNA binding, which, nevertheless, increases the communication strength between NSec63, NRecA2, and CRecA2. As such, RNA binding reinforces the allosteric cross-talk between distal Brr2 functional sites, similar to what is observed in other spliceosome proteins. , Hence, upon RNA/Jab1 binding the intracassette communication is weakened, but a stronger communication channel is established between N- and C-cassette (Figure D–G). In all systems, the links to the community located on CSec63 are weak, indicating this domain is not strongly linked to the rest of Brr2 and, therefore, that this cassette may act as landing pad mediating the binding of other spliceosome proteins, which regulate Brr2 function.…”
supporting
confidence: 75%
“…We next systematically analyzed all differences in the non‐covalent intramolecular interactions among the different Rac1 isoforms using key Interactions Finders program (Crean et al, 2023) (Figure 4). This analysis allows one to gain insights into the interaction‐network remodeling induced by the mutations (Spinello et al, 2023).…”
Section: Resultsmentioning
confidence: 99%